2011
DOI: 10.1039/c1dt10355e
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of 11-vertex rhodathiaboranes: reactions with monodentate phosphines

Abstract: 2Graphical entry and synopsis Reactions of [8, ) 2 -nido-8,7-RhSB 9 H 10 ] (1) with PR 3 afford 11-vertex rhodathiaboranes in which the resulting ligand configuration is driven by the nature of the monodentate phosphine. The lability of some of the species is demonstrated by variable NMR studies, which give mechanistic insights on the substitutional chemistry of 11-vertex nido-rhodathiaboranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 23 publications
3
24
0
Order By: Relevance
“…The same structural motifs are found in the pyridine-ligated analogues, [8,8,8-(H) (2) or PMePh 2 (6) ( Table 1). [5][6]9 Compounds 2-6 are 13 skeletal electron pair clusters (sep) that conform to Wade's rules. 3a This fact contrasts with the precursor 1 that has 12 sep, typical of a closo / isonido cage, but exhibits an 11-vertex nido-structure.…”
Section: Synthesis and Characterization Of Picoline-ligated 11-vertexmentioning
confidence: 99%
See 1 more Smart Citation
“…The same structural motifs are found in the pyridine-ligated analogues, [8,8,8-(H) (2) or PMePh 2 (6) ( Table 1). [5][6]9 Compounds 2-6 are 13 skeletal electron pair clusters (sep) that conform to Wade's rules. 3a This fact contrasts with the precursor 1 that has 12 sep, typical of a closo / isonido cage, but exhibits an 11-vertex nido-structure.…”
Section: Synthesis and Characterization Of Picoline-ligated 11-vertexmentioning
confidence: 99%
“…Reactions with monodentate phosphines led to the formation of metal-ligand-substitution products, [8, )(PPh 3 )-nido-8,7-RhSB 9 H 10 ], as well as compounds resulting from the substitution of the PPh 3 ligands and the addition of a third phosphine at the metal centre, [8,8, ) 3 -nido-8,7-RhSB 9 H 10 ] (Scheme 1). 5 Alternatively, the treatment of 1 with pyridine affords a hydridorhodathiaborane, [8,8,8-(H)(PPh 3 ) 2 -9-(NC 5 H 5 )-nido-8,7-RhSB 9 H 9 ] (2), in which the pyridine ligand binds to boron-9 adjacent to the metal on the pentagonal face (Scheme 1). 6 The bis-PPh 3 -ligated 11-vertex nido-rhodathiaborane, 1, also undergoes substitution reactions with 1,3-dimethylimidazol-2-ylidene, IMe, giving a mixture that contains the products of monosubstitution and disubstitution, [8, )(IMe)-nido-8,7-RhSB 9 H 10 ] and [8, 2 -nido-8,7-RhSB 9 H 10 ] (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests a higher trans influence of a BeH unit vs. a sulphur vertex. This fact has also been observed in 1, and in 11-vertex nidohydridorhodathiaborane derivatives [29,31].…”
Section: Resultsmentioning
confidence: 57%
“…In particular, [8,8- [29]. However, further investigation has revealed that the 10-vertex iridathiaborane [9,9,9,(H)(PMe 3 ) 2 -arachno-9,6-IrSB 8 H 10 ] (5), is also formed as a co-product (ca 7%) by a boron vertex cluster dismantling process (Scheme 2A).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation